Criminalization of Insults the President and Vice President in Indonesia - Dewi Maesyaroh; Sulistyanta Sulistyanta (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Law Number 1 of 2023 about Criminal Code (KUHP), standardizes the criminalization of insults head of state Indonesia, particularly in Articles 217 to 220. The rule is considered contradictory because it can limit criticism toward the government. This study aims to examine regulations akining castigations against the President and Vice President and evaluate the impact of criminalization on freedom of expression and human rights. The research method utilized normative legal research conducted by reviewing literature and focusing on the democracy principles, freedom of speech, and civil rights. The study results show that the criminalization of offences aim the President and Vice is considered a mechanism check and conducive balance, ensuring that criticism against the President is conveyed responsibly without violating ethics, and maintaining the honor and dignity of the president. In conclusion, insulting the President provokes great consequences, in regard to the constitution, freedom of speech is not as limitless, and not absolute and must be rationated by the human rights of others. Therefore the rules concerning the criminalization of insults aim the President and Vice are suitable to maintain stability and public interest and belongs to the process of legal reform.